Pengaruh Kemampuan, Pengalaman dan Independensi Auditor pada Efektivitas Pelaksanaan Prosedur Audit Investigatif - Antonio Lameng, Agung Kresna Yogaswara; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p08, 2018)
The investigative audit aims to identify and uncover fraud by using the approaches, procedures, and techniques commonly used in the investigation of a crime. In order for the investigative audit to produce an objective and significant find, then the investigative audit procedure needs to be carried out effectively. Based on the concepts and results of previous research indicates that the effectiveness of the implementation of investigative audit procedures is influenced by several factors such as ability, experience, and independence of auditors. Implementation of effective investigative audit procedures is often constrained by inadequate ability and experience of auditors in conducting investigative audits, and non-independent auditor attitudes in conducting investigative audits. Therefore, this study aims to empirically test the effect of the ability, experience, and independence of auditor on the effectiveness of the implementation of investigative audit procedures. This research was conducted in Finance and Development Supervisory Board Representatives of Bali. Samples taken as many as 39 auditors, determined by purposive sampling method. Data was collected using questionnaires. Analysis technique used is the Multiple Linear Regression Analysis. Based on the analysis concluded that auditor's ability positive effect on the effectiveness of the implementation of investigative audit procedures, auditor’s experience a positive effect on the effectiveness of the implementation of investigative audit procedures, and auditor’s independence have positive effect on the effectiveness of the implementation of investigative audit procedures. This means that the better auditor's ability, experience, and independence will lead to more effective implementation of investigative audit procedures. Keywords: Auditor’s Ability, Experience of Auditors, Auditor Independence, Effectiveness, Procedure, Investigative Audit